1983
DOI: 10.1111/j.1432-1033.1983.tb07400.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Secreted Protease from Tetrahymena pyriformis

Abstract: A simple major protease, secreted into the medium during growth of Tetrahymenapyrijormis strain W, has been purified about 4000-fold by (NH,),SO, precipitation, ion-exchange chromatography, gel filtration and affinity chromatography on organomercurial-Sepharose. The purified protease was homogeneous as judged by polyacrylamide gel electrophoresis and was a nionomeric protein with a molecular weight of 22000-23000. Amino acid analysis showed that the enzyme was rich in acidic amino acids. In addition, the purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The specific activity for the hydrolysis of HPA at pH 4 compared well with that reported with haemoglobin as substrate (Miiller et al, 1966;Miiller, 1972) whilst the specific activity towards AZC was similar to that reported by others (Suprynowicz & Allewell, 1979;Banno et al, 1982Banno et al, , 1983.…”
Section: Proteolytic Activities Detected and Their Propertiessupporting
confidence: 85%
See 1 more Smart Citation
“…The specific activity for the hydrolysis of HPA at pH 4 compared well with that reported with haemoglobin as substrate (Miiller et al, 1966;Miiller, 1972) whilst the specific activity towards AZC was similar to that reported by others (Suprynowicz & Allewell, 1979;Banno et al, 1982Banno et al, , 1983.…”
Section: Proteolytic Activities Detected and Their Propertiessupporting
confidence: 85%
“…The proteolytic system of the ciliate Tetrahymena pyriformis is probably that most studied amongst protozoan species (Dickie & Liener, 1962;Levy et al, 1976;Banno et al, 1982Banno et al, , 1983. Both acid proteinase and neutral proteinase activities have been described but it is not at all clear how many different types of enzyme are responsible for these.…”
Section: Introductionmentioning
confidence: 99%
“…Other ciliate species such as Tetrahymena pyriformis and T. thermophilia have previously been shown to contain and secrete proteases (Banno et al 1983, Straus et al 1992. In these studies, proteases were suggested to be involved in both intracellular and extracellular digestion.…”
Section: Discussionmentioning
confidence: 99%
“…In the scuticociliate parasite of fish Uronema marinum, Lee et al (2003) detected metalloprotease secretion as early as 10 min in ciliate cell suspensions using fluorescence polarisation. They suggested that the metalloproteases are involved in the pathogenesis of this ciliate infection in fishes.Other ciliate species such as Tetrahymena pyriformis and T. thermophilia have previously been shown to contain and secrete proteases (Banno et al 1983, Straus et al 1992. In these studies, proteases were suggested to be involved in both intracellular and extracellular digestion.…”
mentioning
confidence: 99%
“…Certain heterotrophic bacteria, including pathogenic bacteria, produce extracellular peptidases (Odagami et al 1994;Simoneni and Palva 1993;Worm and Nybroe 2001). Protozoa also secrete peptidases that enhance degradation and uptake of nitrogen sources (Banno et al 1983). Many different peptidases secreted by these microorganisms act to produce oligopeptides and amino acids, which are essential substrates for microorganism growth and are sources of both organic carbon and nitrogen.…”
Section: Introductionmentioning
confidence: 99%